Determinants of spice exports in India: A panel data regression analysis: Determinants of spice exports in India - Vilasini, M; Gopalsamy, S (Journal of Spices and Aromatic Crops, 2025)
This study aims to investigate the determinants of spices namely pepper, cinnamon and clove exports in India using panel data regression analysis, with a focus on the impact of distance, population size, exchange rate of the importing country and import value and volume of the spice imported by India. The secondary data was collected for a period of ten years (2012–2021) and analyzed among the five major spice export markets of India. Our findings suggest that total export volume, exchange rate, and distance between exporting and importing countries have a positive and significant effect on spice exports, while an importing country’s population size has a negative impact. Overall, the study provides insights into the factors that determine spice exports. Our finding may have implications for policymakers, setting export prices, and developing a refined strategy for spice exports from India.